OnabotulinumtoxinA Improves Quality of Life in Chronic Migraine: The PREDICT Study. (5th July 2022) - Boudreau, Guy; Finkelstein, Ian; Graboski, Corrie; Ong, May; Christie, Suzanne; Sommer, Katherine; Bhogal, Meetu; Davidovic, Goran; Becker, Werner J.
ABSTRACT: Background: The PREDICT study assessed real-world, long-term health-related quality of life in adults with chronic migraine (CM) receiving onabotulinumtoxinA. Methods: Canadian, multicenter, prospective, observational study in adults naïve to onabotulinumtoxinA for CM. OnabotulinumtoxinA (155–195 U) was administered every 12 weeks over 2 years (≤7 treatment cycles). Primary endpoint: mean change in Migraine-Specific Quality of Life Questionnaire (MSQ) at treatment 4 (Tx4) versus baseline. Secondary endpoints: mean change in MSQ at final visit versus baseline, and headache days. Results: 184 participants (average age 45 years; 84.8% female; 94.6% Caucasian) received ≥1 onabotulinumtoxinA treatment; 150 participants completed 4 treatments (1 year) and 123 completed all 7 treatment cycles (2 years). Mean (SD) onabotulinumtoxinA dose per treatment cycle was 171 (18) U and treatment interval was 13.2 (1.8) weeks. Baseline mean (SD) 20.9 (6.7) headache days/month decreased (Tx1: −3.5 [6.3]; Tx4: −6.5 [6.6]; p < 0.0001 versus baseline). Mean (SD) increased from baseline in MSQ at Tx4 (restrictive: 21.5 [24.3], preventive: 19.5 [24.7], emotional: 22.9 [32.9]) and the final visit (restrictive: 21.3 [23.0], preventive: 19.2 [23.7], emotional: 27.4 [30.7]), exceeding minimal important differences (all p < 0.0001). Seventy-seven (41.8%) participants reported 168 treatment-emergent adverse events (TEAEs); 38 TEAEs (12.0%) were considered treatment-related. Four (2.2%) participants reported six serious TEAEs; none were considered treatment-related. No new safety signals were identified. Conclusions: Real-world evidence from PREDICT demonstrates that onabotulinumtoxinA for CM in Canada improved MSQ scores and reduced headache frequency and severity, adding to the body of evidence on the long-term safety and effectiveness of onabotulinumtoxinA for CM.